2018
DOI: 10.1016/j.devcel.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Restricted Regulation of Spätzle/Toll Signaling during Cell Competition

Abstract: Cell competition employs comparisons of fitness to selectively eliminate cells sensed as less healthy. In Drosophila, apoptotic elimination of the weaker "loser" cells from growing wing discs is induced by a signaling module consisting of the Toll ligand Spätzle (Spz), several Toll-related receptors, and NF-κB factors. How this module is activated and restricted to competing disc cells is unknown. Here, we use Myc-induced cell competition to demonstrate that loser cell elimination requires local wing disc synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 71 publications
2
87
0
Order By: Relevance
“…After developmental time, indicated in the cartoon with a clock, clones of orange Toll OE cells are growing over a larger percentage of the tissue upon infection (A' and B'). The source of active Spätzle may be both systemic, as suggested by our experiments, and local (20).…”
Section: Survival Analysismentioning
confidence: 55%
See 3 more Smart Citations
“…After developmental time, indicated in the cartoon with a clock, clones of orange Toll OE cells are growing over a larger percentage of the tissue upon infection (A' and B'). The source of active Spätzle may be both systemic, as suggested by our experiments, and local (20).…”
Section: Survival Analysismentioning
confidence: 55%
“…Overexpression (OE) of Cactus in loser cells rescues cell competition-driven elimination of both RpL14 +/-Minute clones and of wild-type clones surrounded by cells with an extra copy of the dMyc gene (16). It has recently been proposed that dMyc-expressing winner cells release Spätzle and the serine proteases required for its activation, thereby enhancing Toll-dependent apoptosis in neighboring loser cells (20).…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the observation that components of innate immunity pathways are required for the elimination of defective cells in Drosophila has led to the hypothesis that this mechanism, which is involved in host defence from foreign or altered-self cells, can be repurposed to eliminate less-fit cells (Alpar et al, 2018;Meyer et al, 2014). The authors of Meyer et al's study observed that, during cell competition, there is a repurposing of Toll-related receptors and NFκB factors, and this repurposing is required for the elimination of losers in Myc-and Minute-induced competition models.…”
Section: Fitness-sensing Cell Competitionmentioning
confidence: 99%